Selling Milan in pieces: the finance-led production of urban spaces. Issue 1 (2nd January 2021) - Mosciaro, Mayra
ABSTRACT: The idea that the city of Milan is being 'sold in pieces', raised by one of the interviewees that collaborated with this study, is the perfect description of the piecemeal contractual urban planning approach that the municipality has relied on for the past decades. This paper will scrutinize the latest large-scale urban redevelopment project in the city, CityLife, and argue that this is the ultimate example of land being mobilized, produced, and negotiated, as a pure financial asset. The process occurring in Milan is not peculiar or unique to this city, as a matter of fact, many of the core elements that support CityLife are widely recognizable: financially constrained local governments in search of new revenue streams and looking to reduce expenses; the transition of non-financial firms into finance-led companies – the rise of shareholder value and other market metrics; the realization that real estate is 'not just another asset class', etc. This paper will rely on CityLife to discuss a growing trend in cities around the world, the financialization of the built environment and the different layers (actors) necessary to promote such finance-led urban '(re)development' schemes.